Hospital and Operator Variation in Cardiac Rehabilitation Referral and Participation After Percutaneous Coronary Intervention: Insights From Blue Cross Blue Shield of Michigan Cardiovascular Consortium. Issue 11 (November 2021) - Sukul, Devraj; Seth, Milan; Thompson, Michael P.; Keteyian, Steven J.; Boyden, Thomas F.; Syrjamaki, John D.; Yaser, Jessica; Likosky, Donald S.; Gurm, Hitinder S.
Abstract : Background: Despite its established benefit and strong endorsement in international guidelines, cardiac rehabilitation (CR) use remains low. Identifying determinants of CR referral and use may help develop targeted policies and quality improvement efforts. We evaluated the variation in CR referral and use across percutaneous coronary intervention (PCI) hospitals and operators. Methods: We performed a retrospective observational cohort study of all patients who underwent PCI at 48 nonfederal Michigan hospitals between January 1, 2012 and March 31, 2018 and who had their PCI clinical registry record linked to administrative claims data. The primary outcomes included in-hospital CR referral and CR participation, defined as at least one outpatient CR visit within 90 days of discharge. Bayesian hierarchical regression models were fit to evaluate the association between PCI hospital and operator with CR referral and use after adjusting for patient characteristics. Results: Among 54 217 patients who underwent PCI, 76.3% received an in-hospital referral for CR, and 27.1% attended CR within 90 days after discharge. There was significant hospital and operator level variation in in-hospital CR referral with median odds ratios of 3.88 (95% credible interval [CI], 3.06–5.42) and 1.64 (95% CI, 1.55–1.75), respectively, and in CR participation with median odds ratios of 1.83 (95% CI, 1.63–2.15) and 1.40 (95% CI, 1.35–1.47), respectively. In-hospital CR referral was significantly associated with an increased likelihood of CR participation (adjusted odds ratio, 1.75 [95% CI, 1.52–2.01]), and this association varied by treating PCI hospital (odds ratio range, 0.92–3.75) and operator (odds ratio range, 1.26–2.82). Conclusions: In-hospital CR referral and 90-day CR use after PCI varied significantly by hospital and operator. The association of in-hospital CR referral with downstream CR use also varied across hospitals and less so across operators suggesting that specific hospitals and operators may more effectively translate CR referrals into downstream use. Understanding the factors that explain this variation will be critical to developing strategies to improve CR participation overall. Abstract : Supplemental Digital Content is available in the text.